OER electrocatalyst and preparation method thereof
By synthesizing the combination of [Fe2Ni(μ3-O)(CH3COO)6] cluster with specific ligands in MOFs, the problem of insufficient performance and stability of OER electrocatalysts is solved, and low-cost and efficient OER electrocatalytic performance is achieved. New solutions are provided for electrolytic water hydrogen production technology.
Patent Information
- Application Number
- CN202411450509.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
The existing OER electrocatalysts have problems with poor electrocatalytic performance and insufficient durability in the process of electrolyzing hydrogen production. In particular, the application of mixed metal clusters in MOFs has not been fully developed, resulting in limited electronic environment changes in the active metal sites. , affects catalytic efficiency and stability.
The mixed solution of ferric nitrate and nickel nitrate was reacted with aqueous sodium acetate to form [Fe2Ni(μ3-O)(CH3COO)6] cluster, and was used to form a specific ligand (terephthalic acid, 2,5-dihydroxy pairs by solvothermal method. Phenthalic acid or biphthalic acid) synthesize OER electrocatalysts with excellent electrocatalytic properties to regulate the electrochemical properties of NiFe-based MOFs.
The OER electrocatalyst with low cost, high efficiency and high stability has been achieved, which significantly improves the electrocatalytic performance and durability, provides a new solution for electrolytic water hydrogen production technology, and reduces the dependence on precious metal catalysts.
Smart Images

Figure CN119285975A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an OER electrocatalyst and a preparation method thereof, and belongs to the technical field of electrocatalysts. Background Art
[0002] Hydrogen energy, as an efficient and green energy source, has been regarded as an important part of the future energy system. As a clean energy conversion method, water electrolysis to produce hydrogen has not only attracted widespread attention worldwide, but also plays a vital role in the field of sustainable energy. Water electrolysis to produce hydrogen technology is the process of decomposing water into hydrogen and oxygen. In the process of water electrolysis to produce hydrogen, the oxygen evolution reaction (OER) occupies a pivotal position. The oxygen evolution reaction is a four-electron, four-proton transfer process. Compared with the hydrogen evolution reaction, it is a slow kinetic process and requires a larger overpotential. Therefore, how to improve the electrocatalytic performance of the oxygen evolution reaction is the key to water electrolysis to produce hydrogen.
[0003] Currently recognized optimal oxygen evolution electrocatalysts include platinum (Pt), iridium (Ir), and ruthenium (Ru). However, they are rare and expensive, which reduces their commercial value. Therefore, researchers have turned to the development of non-precious metal electrocatalysts to reduce costs and seek alternatives. Transition metals such as iron (Fe), cobalt (Co), and nickel (Ni) have become the preferred materials for the study of non-precious metal oxygen evolution electrocatalysts due to their abundant resources and low prices. These commonly used transition metals are combined with non-metallic elements (such as boron, carbon, nitrogen, phosphorus, and sulfur) to form non-precious metal water electrolysis catalysts, which exhibit high cost-effectiveness and environmentally friendly characteristics.
[0004] In recent years, metal-organic framework materials have shown great potential in the field of electrocatalysis due to their many advantages such as adjustable porosity, large specific surface area, and superior metal sites. Many literatures report that they show good electrocatalytic performance such as low overpotential and small Tafel slope. This is mainly due to the rich electrocatalytic active sites of MOF materials, which come from their inherent porosity and hybrid properties. The crystalline properties of metal-organic frameworks enable us to design and adjust them at the molecular level to enhance catalytic activity, but current MOF materials still generally have the problem of poor electrocatalytic performance. In order to improve the electrocatalytic performance of MOF in OER, the development of mixed metal MOFs has become an effective strategy. This approach can improve the activity and durability of MOFs by optimizing electronic and structural properties, making them more effective in energy applications. This strategy is similar to the design ideas of bimetallic oxide electrocatalysts and is expected to provide a new direction for the development of OER electrocatalysts. However, in the prior art, there are few reports on mixed metal clusters in MOFs to improve OER activity without changing the framework, although it may cause a large change in the electronic environment of the active metal sites. In addition, the durability of MOFs as electrocatalysts is crucial, especially in terms of chemical stability during electrocatalysis. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the above-mentioned existing OER electrocatalysts and to provide an OER electrocatalyst and a preparation method thereof. The method has low cost and a wide source of raw materials. The prepared OER electrocatalyst has excellent electrocatalytic performance in OER and has excellent stability.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing an OER electrocatalyst comprises the following steps:
[0008] (1) mixing ferric nitrate nonahydrate and nickel nitrate and dissolving them in deionized water to obtain a mixed solution of ferric nitrate and nickel nitrate, adding a sodium acetate aqueous solution to the mixed solution of ferric nitrate and nickel nitrate, stirring for reaction, filtering, washing, and vacuum drying to obtain a [Fe2Ni(μ3-O)(CH3COO)6] cluster;
[0009] (2) Add [Fe2Ni(μ3-O)(CH3COO)6] clusters into a reactor, then add DMF and stir evenly to obtain a [Fe2Ni(μ3-O)(CH3COO)6] cluster solution. Dissolve the ligand in DMF to obtain a ligand solution. Add the ligand solution to the [Fe2Ni(μ3-O)(CH3COO)6] cluster solution, add glacial acetic acid, mix evenly, and place in an oven to react. After the reaction is completed, filter, wash, and dry to obtain an OER electrocatalyst.
[0010] In step (2), the ligand is selected from any one of terephthalic acid, 2,5-dihydroxyterephthalic acid or biphenyl dicarboxylic acid, more preferably biphenyl dicarboxylic acid.
[0011] Furthermore, in step (1), the molar ratio of the nickel nitrate, iron nitrate nonahydrate and sodium acetate is 5:1:(15-16).
[0012] Furthermore, in step (1), the vacuum drying temperature is 60°C.
[0013] Furthermore, in step (2), the mass ratio of the ligand to the [Fe2Ni(μ3-O)(CH3COO)6] cluster is (0.9-1.3):(1-1.5).
[0014] Furthermore, in step (2), the volume ratio of the glacial acetic acid to the total volume of DMF is (1-2):20.
[0015] Furthermore, in step (2), the reaction temperature is 150° C. and the reaction time is 12 h.
[0016] The OER electrocatalyst prepared by the above method.
[0017] Beneficial effects of the present invention:
[0018] 1) The present invention provides a method for preparing an OER electrocatalyst, first synthesizing a [Fe2Ni(μ3-O)(CH3COO)6] cluster, and then using it as a precursor to synthesize an OER electrocatalyst with a specific morphology by a solvothermal method and a ligand. The method is low-cost, and the prepared OER electrocatalyst exhibits excellent catalytic performance, high efficiency and good stability, providing strong support for the development of water electrolysis hydrogen production technology, and providing new ideas and solutions for solving energy crises and environmental problems.
[0019] 2) Different from the conventional one-step solvothermal synthesis of metal salts and ligands, the present invention adopts a strategy of synthesizing different ligands (terephthalic acid, 2,5-dihydroxyterephthalic acid and diphenyl diphthalic acid) with a precursor [Fe2Ni(μ3-O)(CH3COO)6], a neutral bimetallic cluster, to regulate the electrochemical properties of NiFe-based MOFs, and the obtained OER catalyst has better catalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of the OER electrocatalysts prepared in Examples 1-3;
[0021] Figure 2 IR spectra of the OER electrocatalysts prepared in Examples 1-3;
[0022] Figure 3 TEM image of the OER electrocatalyst prepared in Example 1;
[0023] Figure 4 Elemental analysis diagram of the OER electrocatalyst prepared in Example 1;
[0024] Figure 5 TEM image of the OER electrocatalyst prepared in Example 2;
[0025] Figure 6 Elemental analysis diagram of the OER electrocatalyst prepared in Example 2;
[0026] Figure 7 TEM image of the OER electrocatalyst prepared in Example 3;
[0027] Figure 8 XPS test results of OER electrocatalysts prepared in Examples 1-3
[0028] Fig. 9 LSV curves of electrodes prepared using the OER electrocatalysts of Examples 1-3;
[0029] Fig.10 ECSA curves of electrodes prepared using the OER electrocatalysts of Examples 1-3;
[0030] Fig.11 The electrochemical impedance spectra of the electrodes prepared using the OER electrocatalysts of Examples 1-3 at 500 mV. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings and specific embodiments.
[0032] Example 1
[0033] A method for preparing an OER electrocatalyst comprises the following steps:
[0034] (1) Mix and dissolve ferric nitrate nonahydrate (8 g, 0.02 mol) and nickel nitrate hexahydrate (29 g, 0.1 mol) in 70 mL of deionized water to obtain a mixed solution of ferric nitrate and nickel nitrate; dissolve sodium acetate trihydrate (42 g, 0.31 mol) in 70 mL of deionized water to obtain a sodium acetate aqueous solution; add the sodium acetate aqueous solution to the mixed solution of ferric nitrate and nickel nitrate, stir to react, filter, wash the solid product with deionized water and ethanol twice each, and finally dry it in vacuum at 60° C. to obtain
[0035] [Fe2Ni(μ3-O)(CH3COO)6] cluster;
[0036] (2) 100 mg of [Fe2Ni(μ3-O)(CH3COO)6] cluster was added to the reactor, and then 16 mL of DMF was added and stirred to obtain a [Fe2Ni(μ3-O)(CH3COO)6] cluster solution. The ligand terephthalic acid (83 mg, 0.5 mmol) was dissolved in 4 mL of DMF to obtain a ligand solution. The ligand solution was added to the [Fe2Ni(μ3-O)(CH3COO)6] cluster solution, and 2 mL of glacial acetic acid was added. After stirring and mixing, the mixture was placed in an oven at 150 °C for 12 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an OER electrocatalyst, which was recorded as Fe2Ni-MOF-1.
[0037] Example 2
[0038] In step (2), the ligand used was 2,5-dihydroxyterephthalic acid in an amount of 99 mg (0.5 mmol), and the rest was the same as in Example 1. The obtained OER electrocatalyst was recorded as Fe2Ni-MOF-2.
[0039] Example 3
[0040] In step (2), the ligand used was biphenyl dicarboxylic acid, and the amount used was 121 mg (0.5 mmol), and the rest was the same as in Example 1. The obtained OER electrocatalyst was recorded as Fe2Ni-MOF-3.
[0041] Figure 1 From the XRD patterns of the OER electrocatalysts prepared in Examples 1-3, it can be seen that sharp and obvious peaks are observed at 8.93° and 11.07° for Fe2Ni-MOF-1, sharp and obvious peaks are observed at 6.8° and 11.89° for Fe2Ni-MOF-2, and sharp and obvious peaks are observed at 16.84° for Fe2Ni-MOF-3. Different characteristic diffraction peaks indicate that different organic ligands exhibit different coordination modes. In addition, the experimental results also show that under the same solvothermal conditions, MOFs materials with better crystal forms can be synthesized by Fe2Ni(μ3-O) and different organic ligands.
[0042] Figure 2 The infrared spectra of the OER electrocatalysts prepared in Examples 1-3, wherein Figure 2 (a) is the infrared spectrum of Fe2Ni-MOF-1 prepared in Example 1, Figure 2 (b) is the infrared spectrum of Fe2Ni-MOF-2 prepared in Example 2, Figure 2 (c) is the infrared spectrum of Fe2Ni-MOF-3 prepared in Example 3. It can be seen that in the range of 2500-4000 cm -1 All samples were within 3300cm -1There is a broad peak near 1380cm -1 There are obvious absorption peaks on the left and right, which are the characteristic peaks of benzene ring. The infrared spectra of terephthalic acid, 2,5-dihydroxyterephthalic acid and biphenyl dicarboxylic acid are all at 1670cm -1 There is a peak on the left and right, which is the absorption peak caused by C=O stretching vibration. Due to the conjugation effect with the benzene ring, the wave number decreases to less than 1700cm -1 . At 820cm -1 The peaks near the para-disubstituted benzene ring are 1663, 1585 and 1464 cm -1 The nearby peaks are caused by the vibration of the benzene ring skeleton. By observing the infrared spectra of Fe2Ni-MOF-1, Fe2Ni-MOF-2 and Fe2Ni-MOF-3, it is found that the characteristic peaks corresponding to the infrared spectra of their ligands are consistent, but due to the addition of [Fe2Ni(μ3-O)(CH3COO)6] clusters, the wavenumbers of the corresponding characteristic peaks have decreased. The appearance of these peaks, in contrast to the functional groups of the organic ligands, proves that the structure has not been destroyed during the synthesis process and the original structure is preserved.
[0043] Figure 3 TEM image of the OER electrocatalyst prepared in Example 1, Figure 3 (a) and Figure 3 (b) is a TEM image at different sizes. It can be observed that the Fe2Ni-MOF-1 material shows a prismatic morphology and is relatively dispersed and relatively uniform in size, with a length of about 1.5 to 2 μm and a width of about 250 nm.
[0044] Figure 4 This is the elemental analysis diagram of the OER electrocatalyst prepared in Example 1. The elemental analysis diagram proves that the material is composed of C, O, Fe and Ni elements. Combined with the element proportion table, it can be seen that Fe is about 3.32%, Ni is about 1.51%, and the atomic ratio is 2.20:1, which is consistent with the Fe2Ni ratio of 2:1 in the feed.
[0045] Figure 5 From the TEM image of the OER electrocatalyst prepared in Example 2, it can be seen that Fe2Ni-MOF-2 is in the form of smaller particles, and a small number of particles are aggregated together, presenting an irregular elliptical or irregular shape. The dispersion is relatively uniform, with a length of 40 to 200 nm and a width of 20 to 60 nm.
[0046] Figure 6The elemental analysis of the OER electrocatalyst prepared in Example 2 shows that Fe is about 27.06%, Ni is about 13.53%, and Fe:Ni=1.996:1, which is consistent with the input Fe2Ni, and the result is in line with the design. Compared with the Fe2Ni-MOF-1 prepared in Example 1, the metal proportion is increased, and the number of unsaturated metal active sites is increased, which is conducive to improving the electrocatalytic efficiency.
[0047] Figure 7 TEM image of the OER electrocatalyst prepared in Example 3, Figure 7 (a) and Figure 7 (b) are TEM images at different sizes. It can be seen that Fe2Ni-MOF-3 is mostly in flake form and relatively scattered. It is combined into a whole and presents an irregular band shape. The dispersion is relatively uniform, with a length of 0.2 to 2 μm and a width of 200 to 500 nm.
[0048] Figure 8 The XPS test results of the OER electrocatalysts prepared in Examples 1-3 are as follows: Figure 8 (a) is the Fe2p diagram of Fe2Ni-MOF-1. It can be seen from the figure that the Fe 2p3 / 2 peak is located at about 711.49 eV, and the Fe 2p1 / 2 peak is located at about 724.96 eV. The energy difference between these two peaks is about 13.5 eV, which is very consistent with the XPS standard peak of iron. Therefore, it can be confirmed that there is iron in the sample, indicating that iron is successfully doped into the prepared sample; Figure 8 (b) is the Fe 2p diagram of Fe2Ni-MOF-2. It can be seen from the figure that the peak of Fe 2p3 / 2 is located at about 711.62eV, and the peak of Fe 2p1 / 2 is located at about 724.79eV. The energy difference between these two peaks is about 13.2eV, which is consistent with the typical XPS peak splitting characteristics of iron; Figure 8 (c) is the Fe2p diagram of Fe2Ni-MOF-3. It can be seen from the figure that the Fe 2p3 / 2 peak is located at about 711.70eV, the Fe 2p1 / 2 peak is located at about 725.02eV, and the difference between the two peaks is about 13.3eV. Through these peaks, we can confirm that iron does exist in the sample. Figure 8 (d) is the Ni 2p diagram of Fe2Ni-MOF-1. It can be seen from the figure that the Ni2p3 / 2 peak is located at about 856.04, the Ni 2p1 / 2 peak is located at about 873.59 eV, and the energy splitting between these two peaks is about 17.55 eV; Figure 8 (e) is the Ni 2p diagram of Fe2Ni-MOF-2. It can be seen from the figure that the Ni2p3 / 2 peak is located at about 856.10, the Ni 2p1 / 2 peak is located at about 873.53 eV, and the energy splitting between these two peaks is about 17.4 eV; Figure 8 (f) is the Ni 2p diagram of Fe2Ni-MOF-3. From the diagram, we can see that the Ni 2p3 / 2 peak is located at about 856.22, the Ni2p1 / 2 peak is located at about 873.93 eV, and the energy splitting between these two peaks is about 17.7 eV. Combined with the analysis of these energy differences, nickel is present in all samples.
[0049] The OER electrocatalysts prepared in Examples 1-3 were prepared into electrodes, and then the electrocatalytic performance was tested:
[0050] 1) Preparation of the electrode: Weigh 5 mg of OER electrocatalyst and 5 mg of carbon black and place them in a centrifuge tube. Use a pipette to extract 900 μL of isopropanol to disperse the contents of the tube, and then ultrasonicate for 30 minutes. Next, use a pipette to add 50 μL of nafion solution to the tube twice, and wait for ultrasonication for 30 minutes to ensure sufficient mixing. After the second ultrasonication, add another 50 μL of nafion solution to prevent the sample from falling off, and continue ultrasonication for 20 minutes. After the ultrasonication is completed, the mixture in the centrifuge tube should form a uniform ink slurry. Next, use a pipette to draw 2.5 μL of ink slurry twice and apply it to the working electrode, and air-dry at room temperature after each coating. Repeat this operation until the ink slurry reaches 10 μL. Before testing, immerse the working electrode in a 1 mol / L KOH solution to check whether the catalyst has fallen off, and then use an ear-washing bulb to blow away excess electrolyte before starting the test.
[0051] 2) Electrolytic cell and test device: The experimental data collection and performance image observation were performed using the Shanghai Chenhua electrochemical workstation model CHI760E. The performance test was carried out using a three-electrode system, in which the reference electrode was a Hg / HgO electrode, the counter electrode was a platinum electrode, and the working electrode was a glassy carbon electrode with an inner diameter of 5 mm. The purpose of this experiment was to test the kinetic performance of the OER reaction under alkaline conditions, and the electrolyte used was a 1 mol / L KOH solution with a pH value of 14.
[0052] 3) Linear sweep voltammetry (LSV) test: 5mV s -1 Linear sweep voltammetry was recorded at a scan rate of 100 0.0 ... RHE =E Hg / HgO+0.098+0.0592×pH. Overpotential (η) is calculated according to the formula η=E RHE -1.23V calculated.
[0053] 4) Electrochemically active surface area (ECSA) test: The electrochemically active surface area (ECSA) can be measured based on the electrochemical double layer capacitance (C dl ) for evaluation.dl The results are obtained by scanning at different scan rates (v = 10, 20, 30, 40 and 50 mVs -1 ) is calculated from the cyclic voltammograms tested in the potential range of 0.096 V for the initial voltage to 0.196 V for the final voltage vs Hg / HgO. According to equation C dl =Ic / v Fit the current difference at 0.146V to obtain C dl , where Ic and v are the charging current (mAcm -2 ) and scan rate (mV s -1 ).
[0054] 5) Electrochemical impedance spectroscopy (EIS) test.
[0055] Fig. 9 is the LSV curve of the electrode prepared using the OER electrocatalyst of Examples 1-3, wherein Fig. 9 (a) is the LSV curve, Fig. 9 (b) is at 10 mA·cm -2 The overpotential under Fig. 9 (c) is the Tafel slope diagram. It can be seen that the electrochemical performance of Fe2Ni-MOF-1, Fe2Ni-MOF-2 and Fe2Ni-MOF-3 is better. Fig. 9 (b) It can be seen that Fe2Ni-MOF-1, Fe2Ni-MOF-2 and Fe2Ni-MOF-3 have a high -2 The overpotentials under the conditions of 297mV, 284.8mV and 283.8mV are respectively. The smaller the overpotential value, the better the catalytic performance. Fe2Ni-MOF-3 performs better than the other two polymers. Combined with the Tafel slope graph, the tafel slope is obtained through linear fitting. The smaller the tafel slope, the more outstanding the kinetic performance of the material, indicating that the electrochemical kinetics of Fe2Ni-MOF-3 is also excellent.
[0056] Fig.10 is the ECSA curve of the electrode prepared using the OER electrocatalyst of Examples 1-3, wherein Fig.10 (a) Fig.10 (b) Fig.10 (c) ECSA curves of Fe2Ni-MOF-1, Fe2Ni-MOF-2 and Fe2Ni-MOF-3, respectively. Fig.10 (d) C of Fe2Ni-MOF-1, Fe2Ni-MOF-2 and Fe2Ni-MOF-3 at 0.146 V dl , in the figure, C dl stands for electrochemical double layer capacitance, and ECSA stands for electrochemically active surface area. According to the formula, Cdl The relationship between Cdl and ECSA can be converted by the following formula: ECSA = Cdl / Cs, where C(s) is the specific capacitance of the corresponding surface smooth sample under the same conditions. Therefore, Cdl can be converted to ECSA by this formula. According to the analysis, the double layer capacitance (C dl ) is the highest among the catalysts, indicating that Fe2Ni-MOF-3 has a higher intrinsic activity and a stronger ability of the capacitor to store charge.
[0057] Fig.11 The electrochemical impedance spectra of the electrodes prepared using the OER electrocatalysts of Examples 1-3 at 500 mV show that Fe2Ni-MOF-3 has a smaller semicircle radius than Fe2Ni-MOF-1 and Fe2Ni-MOF-2, indicating that it has lower charge transfer resistance and faster electrocatalytic kinetics. Therefore, Fe2Ni-MOF-3 is superior to Fe2Ni-MOF-1 and Fe2Ni-MOF-2 in terms of OER activity, and has higher catalytic efficiency and kinetics.
Claims
1. A method for preparing an OER electrocatalyst, characterized in that: The steps include: (1) mixing ferric nitrate nonahydrate and nickel nitrate hexahydrate and dissolving them in deionized water to obtain a mixed solution of ferric nitrate and nickel nitrate, adding a sodium acetate aqueous solution to the mixed solution of ferric nitrate and nickel nitrate, stirring for reaction, filtering, washing, and vacuum drying to obtain a [Fe2Ni(μ3-O)(CH3COO)6] cluster; (2) adding [Fe2Ni(μ3-O)(CH3COO)6] clusters into a reactor, then adding DMF and stirring evenly to obtain a [Fe2Ni(μ3-O)(CH3COO)6] cluster solution, dissolving the ligand in DMF to obtain a ligand solution, adding the ligand solution to the [Fe2Ni(μ3-O)(CH3COO)6] cluster solution, then adding glacial acetic acid, mixing evenly, placing in an oven for reaction, filtering, washing, and drying after completion to obtain an OER electrocatalyst; In step (2), the ligand is selected from any one of terephthalic acid, 2,5-dihydroxyterephthalic acid or biphenyl diphthalic acid.
2. The method for preparing an OER electrocatalyst according to claim 1, characterized in that: In step (1), the molar ratio of nickel nitrate, iron nitrate nonahydrate and sodium acetate is 5:1:(15-16).
3. The method for preparing an OER electrocatalyst according to claim 1, characterized in that: In step (1), the vacuum drying temperature is 60°C.
4. The method for preparing an OER electrocatalyst according to claim 1, wherein: In step (2), the mass ratio of the ligand to the [Fe2Ni(μ3-O)(CH3COO)6] cluster is (0.9-1.3):(1-1.5).
5. The method for preparing an OER electrocatalyst according to claim 1, wherein: In step (2), the volume ratio of the glacial acetic acid to the total volume of DMF is (1-2):
20.
6. The method for preparing an OER electrocatalyst according to claim 1, characterized in that: In step (2), the reaction temperature is 150° C. and the reaction time is 12 h.
7. The method for preparing an OER electrocatalyst according to any one of claims 1 to 6, characterized in that: In step (2), the ligand is biphenyl dicarboxylic acid.
8. An OER electrocatalyst prepared by the method according to any one of claims 1 to 7.